2023
DOI: 10.59249/earx2427
|View full text |Cite
|
Sign up to set email alerts
|

Eco-emotions and Psychoterratic Syndromes: Reshaping Mental Health Assessment Under Climate Change

Abstract: Human activities like greenhouse gas emissions, pollution, and deforestation are largely responsible for climate change and biodiversity loss. The climate is a complex system and scientists are striving to predict, prevent, and address the aforementioned issues in order to avoid reaching tipping points. The threat to humankind is not only physical (ie, heat waves, floods, droughts) but also psychological, especially for some groups. Insecurity, danger, chaos, and an unstable system due to climate change have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…In recent years, a few scales have been developed specifically to measure eco-emotions. A comprehensive search by Cianconi et al 5 identified ten validated psychometric tests for assessing eco-emotions and psychoterratic syndromes; measuring specifically eco-anxiety, eco-grief and solastalgia (e.g., The Hogg Eco-Anxiety Scale 26 ) Nevertheless, further testing, validation and use of those scales in surveys, and ideally in cohort studies including also suicidal ideation and behaviour, is encouraged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a few scales have been developed specifically to measure eco-emotions. A comprehensive search by Cianconi et al 5 identified ten validated psychometric tests for assessing eco-emotions and psychoterratic syndromes; measuring specifically eco-anxiety, eco-grief and solastalgia (e.g., The Hogg Eco-Anxiety Scale 26 ) Nevertheless, further testing, validation and use of those scales in surveys, and ideally in cohort studies including also suicidal ideation and behaviour, is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…The most described eco-emotions in the literature include eco-anxiety, eco-grief, and solastalgia. 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,1825 Climate change anxiety, climate anxiety, climate change worry, or environmental anxiety are often used interchangeably; in some studies, however, it was suggested that climate change anxiety is a subset of eco-anxiety. 17 Eco-anxiety and eco-grief exhibit distinct characteristics: eco-anxiety is primarily focused on the future, reacting to anticipated ecological losses, while eco-grief is more centred around real or past ecological losses, or reactions to future situations causing current losses 14 . Eco-grief resonates strongly with solastalgia.…”
Section: Introductionmentioning
confidence: 99%
“…26 Often eco-anxiety has been used as an umbrella term capturing all these related emotions. 22,27 Yet disagreements regarding the definition of this concept continue 14 implying that the understanding of these phenomena is still in the process of development. 28 Other concepts that encapsulate some eco-emotions are also found in the literature, such as eco-coping, eco-concern, and eco-uncertainty (Box 1).…”
Section: Introductionmentioning
confidence: 99%